Right internal jugular vein phlebectasia-a rare cause of neck swelling in paediatric population - Jayakumar, Varunkumar; Arora, Priyanka Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Reporting a case of an 8-year-old boy presenting with a right neck swelling appearing on straining which otherwise not seen with a diagnosis of right internal jugular vein phlebectasia. Paediatric population with neck swellings more commonly misdiagnosed clinically and hence with non-invasive radiological investigations like Ultrasonography with colour doppler and contrast enhanced computed tomography was done to confirm the diagnosis. Phlebectasias are at times incidental findings and stay asymptomatic, hence proper diagnosis with radiological investigations is needed as they are misdiagnosed with other neck swellings. Only few cases of internal jugular vein phlebectasias have been reported and approximately 20 cases have undergone surgery for cosmetic purposed and majority were managed conservatively like in our case report. This needs to be kept as a differential diagnosis in a paediatric patient presenting with neck swelling.